Malonate catabolism does not drive N2 fixation in legume nodules. - Karunakaran, R; East, A; Poole, P (2013)
Malonyl-coenzyme A (CoA) decarboxylase, malonyl-CoA synthetase, and malonate transporter mutants of Rhizobium leguminosarum bv. viciae and trifolii fixed N2 at wild-type rates on pea and clover, respectively. Thus, malonate does not drive N2 fixation in legume nodules.